PENGARUH LINGKUNGAN TERHADAP PERKEMBANGAN BAHASA ANAK - Azwar Anas; Sinta Aida Farhatulmillah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2018)
Children's language always undergoes a development process, either in the form of good or bad development. The environment can affect the process of language development in children. Every child has a great sense of curiosity, where he is still free to imagine, has the courage to do new things, and is tireless, so the factors from friends and the environment greatly support the process of children's language development. the cause of whether the language development process is good or not depends on the factors in the surrounding environment, as well as on how long the child lives in that environment. Because the length of time makes children accustomed to and trained on the environmental influences they get